(untitled) (Research, Society and Development, 2022)
Ain: To carry out, through an integrative review, an analysis of published studies that deal with the importance of the insertion of the dental surgeon (CD) in the multidisciplinary team of palliative care in oncopediatric patients. Methodology: Integrative review of studies published in the last 20 years (2001 to 2021), sampled children from 0 to 18 years old. Articles published in electronic databases: VHL (Virtual Health Library), including US National Library of Medicine (PubMed) and Scientific Electronic Library Online (Scielo). Results: Eleven articles were included in this review. The studies included in this review are mostly in English. The most common outcomes in relation to oral health were oral mucositis, xerostomia and dental caries. Other studies observed the presence of oral candidiasis and gingivitis as one of the sets of outcomes, not being treated in isolation. Conclusion: The presence of CD during treatment is necessary, since early detection can reduce the consequences of radiotherapy and chemotherapy treatments, and improve quality of life.